Kontribusi Pendidikan Islam dalam Membentuk Keperibadian Islami - Samsul Hakim (Jurnal Al-Amin: Kajian Pendidikan dan Sosial Kemasyarakatan, 2020)
Education as one of the important instruments in Islam in realizing the function of Islam as Rahmatanlil'alamin in the context of Islam is revealed as a solution to all the problems of life faced by humans on earth, whether it is related to faith, morals, intellectuality, sociology, politics or psychology, so that humans get grace and salvation in his life on earth and his life in the afterlife. Grace and Salvation in life will be realized when each individual who is part of society has a complete personality that is in accordance with the guidance and teachings of Islam. This is because personality is the basis for self-identification which is also the control for every individual Muslim in controlling lust and behavior that is not praiseworthy and gives direction to do the right thing in accordance with Islamic rules and regulations.This study aims to examine the contribution of Islamic education in shaping Islamic personality. This type of research is literature research with a qualitative approach, namely by observing and studying books and literature that discuss Islamic education and Islamic personality. Data analysis in this research is content analysis, which is a data analysis technique that discusses in depth the content of information written in printed media, books or other literatures.Based on the description of data and discussion of the contribution of Islamic education in shaping Islamic personality, it can be concluded that Islamic education has an important contribution in shaping Islamic personality and things that are important in Islamic education which are at the same time as the core of Islamic teachings which have an important role in shaping Islamic personality. teachings about: Submit yourself to Allah SWT. Freedom and human dignity and liberating the Muslim person from the factors of fear.